CURC abstract booklet, April 17, 2025 - Colorado State University. JUR Press, publisher (Colorado State University. Libraries, 2025)
Abstracts from the CURC 2025 Showcase.
CURC abstract booklet 2025
Celebrate Undergraduate Research and Creativity abstract booklet, April 17, 2025
CURC 2025 is generously supported by the Office for Undergraduate Research and Artistry (OURA) and The Institute for Learning and Teaching (TILT).
Keywords: Colorado State University -- Undergraduates -- Research; Undergraduates -- Research -- Colorado -- Fort Collins